Impacts of QR codes on buying decision process of Turkish consumers - (:unkn) unknown (Inderscience Publishers, 2015)
Widespread usage of mobile technologies and devices in the last few years led companies to mobilise their marketing processes. One of the new technologies that can be used in mobile marketing is QR codes. Analysing the impact of QR codes on buying decision of consumers may help firms to use these codes in marketing campaigns. This study aims to investigate the extent at which QR codes can have impact on the buying decision process of consumers. Thus, a research model is developed, which proposes that QR codes have a positive impact on the information search and purchase decision both. This model also proposes that information gained by QR code scanning leads to the buying decision. The model defines easy and fast information access, information amount and content accessed via QR codes as factors that affect the information search process. The results of analyses show a significant impact of need recognition and easy information access on the purchase decision along with supporting all the hypothesised relationships. Copyright © 2015 Inderscience Enterprises Ltd.
Keywords: Buying decision process; Information search; Mobile marketing; Need recognition; Opportunity recognition; Purchase decision; QR code; Quick response code